Comparison of Ti–35Nb–7Zr–5Ta and Ti–6Al–4V hydrofluoric acid/magnesium-doped surfaces obtained by anodizing - Reis, Bárbara A. [UNESP]; Fais, Laiza MG. [UNESP]; Ribeiro, Ana L.R. [UNESP]; Vaz, Luis G. [UNESP] (My University, 2020)
Objectives: Development of a new generation of stable β alloy, free of aluminum or vanadium and with better biological and mechanical compatibility and evaluate the surface properties of Ti–6Al–4V and Ti–35Nb–7Zr–5Ta after anodization in hydrofluoric acid, followed by deposition of different electrolyte concentrations of magnesium particles by micro arc-oxidation treatment. Methods: Disks were anodized in hydrofluoric acid. After this first anodization, the specimens received the deposition of magnesium using different concentration (8.5% and 12.5%) and times (30s and 60s). The surface morphology was assessed using scanning electron microscopy, and the chemical composition was assessed using energy dispersive x ray spectroscopy. The surface free energy was measured from the contact angle, and the mean roughness was measured using a digital profilometer. Results: Anodization in hydrofluoric acid provided the formation of nanotubes in both alloys, and the best concentration of magnesium considered was 8.5%, as it was the condition where the magnesium was incorporated without covering the morphology of the nanotubes. X-ray dispersive energy spectroscopy showed magnesium incorporation in all conditions. The average roughness was increased in the Ti–35Nb–7Zr–5Ta alloy. Conclusions: It was concluded that anodizing could be used to deposit magnesium on the surfaces of Ti–6Al–4V and Ti–35Nb–7Zr–5Ta nanotubes, with better results obtained in samples with magnesium concentration in 8.5% and the process favored the roughness in the Ti–35Nb–7Zr–5Ta group.

Materials Science; Nanotechnology; Metallurgical Engineering; Dentistry; Alloys; Titanium; Nanotubes; Magnesium; Dental Implants.
Keywords: Alloys; Dental implants; Dentistry; Magnesium; Materials science; Metallurgical engineering; Nanotechnology; Nanotubes; Titanium